Bioactive α-Pyrone Derivatives from the Endophytic Fungus Diaporthe sp. CB10100 as Inducible Nitric Oxide Synthase Inhibitors - Pu, Hong; Liu, Jianxin; Wang, Yeji; Peng, Yuhui; Zheng, Wanying; Tang, Yang; Hui, Boping; Nie, Chunmei; Huang, Xueshuang; Duan, Yanwen; Huang, Yong (Frontiers in Chemistry, 2021)
Inducible nitric oxide synthase (iNOS) produces NO from L-arginine and plays critical roles in inflammation and immune activation. Selective and potent iNOS inhibitors may be potentially used in many indications, such as rheumatoid arthritis, pain, and neurodegeration. In the current study, five new compounds, including a dibenzo -α - pyrone derivative ellagic acid B (5) and four α-pyrones diaporpyrone A – D (9 – 12), together with three known compounds (6 – 8), were isolated from the endophytic fungus Diaporthe sp. CB10100. The structures of these new natural products were unambiguously elucidated using NMR, HRESIMS or electronic circular dichroism calculations. Ellagic acid B (5) features a tetracyclic 6/6/6/6 ring system with a fused 2H-chromene, which is different from ellagic acid (4) with a fused 2H-chromen-2-one. Both 2-hydroxy-alternariol (6) and alternariol (7) reduced the expression of iNOS at protein levels in a dose-dependent manner, using a lipopolysaccharide (LPS)-induced RAW264.7 cell models. Also, they decreased the protein expression levels of pro-inflammatory cytokines, such as tumor necrosis factor- α, interleukin-6 and monocyte chemotactic protein 1. Importantly, 6 and 7 significantly reduced the production of NO as low as 10 μM in LPS-induced RAW264.7 cells. Molecular docking of 6 and 7 to iNOS further suggests that both of them may interact with iNOS. Our study suggests that 6 and 7, as well as the alternariol scaffold may be further developed as potential iNOS inhibitors.